PENGARUH FIRM SIZE, LEVERAGE, SALES GROWTH, PROFITABILITAS TERHADAP TAX AVOIDANCE (STUDI KASUS PADA PERUSAHAAN FARMASI YANG TERDAFTAR DI BEI) - Erna Diyastuti; Nur Kholis (GEMA, 2022)
The purpose of the research is to understand the effect of Firm Size, Leverage, Sales Growth and Profitability on Tax Avoidance in pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. This research uses secondary data where the sampling technique is using purposive sampling technique, the samples used in the research are 11 companies in the pharmaceutical sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021, then 31 data are obtained which are used for research implementation samples. . The source of data in this study was obtained from the website (www.idx.co.id). The implementation of the following research uses a multiple linear regression model using SPSS 19 to carry out an analysis of the effect of the independent variables on the dependent variable used in the research implementation. The results obtained from the following research activities show that firm size and profitability have no effect on efforts to avoid tax or tax avoidance. Meanwhile, leverage and sales growth have an effect on tax avoidance